Autonomous learning of English pronunciation through vlogs: evidence from two Indonesian EFL students - Siti Fatimah, Asri; Nurul Fitria, Ita; Saputra, Yuyus; Gafar Auliya, Acep; Demir, Kemal (Universitas Muhammadiyah Sidoarjo, 2024)
The growing popularity of Vlogs, particularly on platforms like YouTube, offers avaluable medium for English as Foreign Language (EFL) learners to autonomously improve their English pronunciation outside the classroom. This study aims to describe how students enhance their English pronunciation through English language vlogs. A descriptive case study approach was utilized, involving two students majoring in English Education at a university in Tasikmalaya, West Java, Indonesia. Data were collected through semi structured interviews and analyzed using thematic analysis. The findings indicate that the students employed several strategies to learn English pronunciation via vlogs, including (1) memorizing word pronunciation through repetition; (2) comprehending and applying English language skills from vlogs; (3) utilizing technological tools for assisstance; and (4) engaging in English Communication with others as a means of practical application. The study concludes that students utilize a variety of strategies to improve their English pronunciation through vlogs. Applying these strategies appears to facilitate learning, and enhance their pronunciation. HIGHLIGHTS: Repetition as a Key Strategy: Students relied on repetition to memorize and reinforce the pronunciation of new words learned through vlogs Technology as a Support Tool: The use of technological tools like online dictionaries and Google Translate helped students overcome pronunciation challenges and enhance their autonomous learning process. Social Interaction for Practice: Students applied the pronunciation skills they learned from vlogs in real-life conversations with peers to strengthen their learning through practical use.